2021
DOI: 10.1016/j.neo.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Eucannabinolide, a novel sesquiterpene lactone, suppresses the growth, metastasis and BCSCS-like traits of TNBC via inactivation of STAT3

Abstract: Highlights Euc decreased expression of p-STAT3 (Tyr705), nuclear translocation and DNA-binding. Euc inhibited cell viability, metastasis and BCSC-like traits by inhibiting STAT3. Euc covalently interacted with STAT3 through a Michael addition reaction. Euc exhibits potent anti-tumor growth and lung metastasis without acute toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…SRC-mediated cellular signaling can affect the proliferation, survival, migration, and invasion of TNBC cells [27]. In TNBC, suppression of STAT3 expression inhibited tumor proliferation and migration [28]. Additionally, HRAS [29] and MAPK1 [30] levels were significantly increased in TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…SRC-mediated cellular signaling can affect the proliferation, survival, migration, and invasion of TNBC cells [27]. In TNBC, suppression of STAT3 expression inhibited tumor proliferation and migration [28]. Additionally, HRAS [29] and MAPK1 [30] levels were significantly increased in TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a wide array of small molecules that exhibit the potential to inhibit TNBC cell viability. This includes Dihydrotanshinone ( 166 ), DT-13 ( 167 ), Cucurbitacin E ( 168 – 170 ), Niclosamide ( 171 – 173 ), SG-1709 ( 174 ), SG-1721 ( 174 ), Nifuroxazide ( 175 , 176 ), LLY17 ( 177 ), 6Br-6a ( 178 ), Pyrimethamine ( 179 , 180 ), Pectolinarigenin ( 181 ), Flubendazole ( 182 , 183 ), Eupalinolide J ( 184 , 185 ), Betulinic acid ( 186 ), Carfilzomib ( 187 ), WP1066 ( 188 ), Rhus coriaria extract ( 189 ), FZU-03,010 ( 190 ), Disulfiram ( 191 ), Schisandrin B ( 192 ), Osthole ( 193 ), Brevilin A ( 194 ), Arnicolide D ( 195 ), Eucannabinolide ( 196 ), Pulvomycin ( 197 ), R001 ( 198 ), Salinomycin ( 199 , 200 ), the ethanolic extract of origanum syriacum ( 201 ), Apigenin ( 202 ), and AG-014699 ( 203 ). This inhibition is attributed to their ability to suppress STAT3 phosphorylation.…”
Section: Current Therapeutic Applications Of the Jak2/stat3 Signaling...mentioning
confidence: 99%
“…On the one hand, chemotherapeutic drugs could promote the cleavage of gasdermin E (GSDME) by activating Caspase-3, to transform apoptosis into pyroptosis and promote tumor cell death [ 256 , 257 ]. Likewise, tetraarsenic hexoxide (As 4 O 6 ) could inhibit the phosphorylation of mitochondrial STAT3 and activate mitochondrial ROS-mediated GSDME pathway, to induce pyroptotic cell death in TNBC cells, and finally inhibit tumor growth and metastasis of TNBC [ 258 , 259 ]. On the other hand, chemotherapeutic drugs also played an anti-TNBC role by inducing pyroptosis [ 260 ].…”
Section: Targeting Other Rcd Subroutines With Small-molecule Compound...mentioning
confidence: 99%